2012
DOI: 10.3892/ol.2012.898
|View full text |Cite
|
Sign up to set email alerts
|

Bak is a key molecule in apoptosis induced by methanol extracts of Codonopsis lanceolata and Tricholoma matsutake in HSC-2 human oral cancer cells

Abstract: Abstract. Since the 5-year survival rate of oral cancer remains low, more effective and non-toxic therapeutic and preventive strategies are required. Certain natural products possess anticancer properties. The present study investigated the effects of the methanol extracts of Codonopsis lanceolata (MECI) and Tricholoma matsutake (METM) and identified the molecular target in HSC-2 human oral cancer cells. The results revealed that MECI and METM inhibited growth and induced apoptosis, as demonstrated by poly (AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Several types of Codonopsis extracts have shown anticancer activities. Notably a methanolic extract from C. lanceolata was found to inhibit cancer proliferation and to induce apoptosis of HSC-2 human oral cancer cells in vitro, with an increased expression of the protein Bak [ 46 ]. Also, a n-butanol fraction of C. lanceolata was found to dose-dependently inhibit the growth of HT-29 human colon cancer cells, via the production of intracellular reactive oxygen species (ROS) and polyamine depletion, leading to the induction of cell apoptosis [ 47 ].…”
Section: Anticancer Activity Of Codonopsis Extractsmentioning
confidence: 99%
“…Several types of Codonopsis extracts have shown anticancer activities. Notably a methanolic extract from C. lanceolata was found to inhibit cancer proliferation and to induce apoptosis of HSC-2 human oral cancer cells in vitro, with an increased expression of the protein Bak [ 46 ]. Also, a n-butanol fraction of C. lanceolata was found to dose-dependently inhibit the growth of HT-29 human colon cancer cells, via the production of intracellular reactive oxygen species (ROS) and polyamine depletion, leading to the induction of cell apoptosis [ 47 ].…”
Section: Anticancer Activity Of Codonopsis Extractsmentioning
confidence: 99%
“…Prior to this investigation, several studies confirmed that steaming and the fermentation process significantly improved the cognitive-enhancement and neuroprotective effects of C. lanceolata [ 7 , 20 , 21 ]. In addition, recent studies have indicated that the extract of C. lanceolata exerted inhibition activities on HSC-2 (Hematopoietic Stem Cell-2) human oral cancer cells and HT-29 human colon cancer cell [ 22 , 23 ]. However, the anti-tumor efficacy in vivo of steamed C .…”
Section: Introductionmentioning
confidence: 99%
“…The current treatments for oral cancer are inadequate and a significant proportion of oral cancer patients may develop local invasion and metastases (11). Numerous studies have been performed to find novel agents (especial from natural plant) which can trigger programmed cell death (apoptosis) in tumor cells and hopefully to provide a new therapeutic approach for anticancer design (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%